2021
DOI: 10.1039/d0md00284d
|View full text |Cite
|
Sign up to set email alerts
|

Peptide directed phthalocyanine–gold nanoparticles for selective photodynamic therapy of EGFR overexpressing cancers

Abstract: Gold nanoparticles, covalently functionalised with the photosensitiser C11Pc and PEG, were actively targeted towards epidermal growth factor receptor overexpressing cancers using the peptide FITC-βAAEYLRK, with selective phototoxicty observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Of these, AEYLR is of particular interest, as it shows a high binding affinity towards EGFR. The latter was conjugated to a 4 nm AuNP with a self-assembled mixed monolayer of the photosensitizer zinc phthalocyanine C11Pc and PEG [117]. The covalent binding of all components of this nanocarrier avoids any off-target phototoxicity due to desorption of the photosensitizer.…”
Section: Egfr-targeting Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, AEYLR is of particular interest, as it shows a high binding affinity towards EGFR. The latter was conjugated to a 4 nm AuNP with a self-assembled mixed monolayer of the photosensitizer zinc phthalocyanine C11Pc and PEG [117]. The covalent binding of all components of this nanocarrier avoids any off-target phototoxicity due to desorption of the photosensitizer.…”
Section: Egfr-targeting Peptidesmentioning
confidence: 99%
“…Moreover, the EGFR-targeting peptide AEYLR was modified with a lysine residue at the C-terminus to allow the conjugation to the PEG (HS-PEG-COOH), and with a FITC-βAla at the N-terminus, allowing for imaging. This targeted nanosystem produces singlet oxygen upon irradiation at 633 nm, and a selective phototoxicity was observed for EGFR-overexpressing cells, displaying nanomolar potency and minimal dark toxicity [117].…”
Section: Egfr-targeting Peptidesmentioning
confidence: 99%
“…No phototoxic response was recorded when the cells were incubated with non-targeted C11Pc-PEG-AuNps. It was concluded that the phototoxicity of peptide-C11Pc-PEG-AuNps was due to the dual effect of photocatalytic activity of C11Pc and the targeting effect [ 97 ]. Shiao et al developed gold nanoparticles modified with aptamer for co-drug delivery in photodynamic therapy.…”
Section: Inorganic and Organic Nanoparticulate For Active Or Passive ...mentioning
confidence: 99%
“…In another study, AuNPs were conjugated with a PS C11Pc and an EGFR peptide AEYLR to target EGFR markers expressed in lung cancer [ 86 ]. The study showed improved PDT effects, no dark toxicity, and the efficiency of a peptide as an excellent option for the delivery of AuNP-PS to tumor cells.…”
Section: Gold Nanoparticle Bioconjugates For Active Targeted Photodyn...mentioning
confidence: 99%